Examination of the Effects of Model-Based Inquiry on Students' Outcomes: Scientific Process Skills and Conceptual Knowledge - BEKİROĞLU, FERAL (ELSEVIER SCIENCE BV, 2014)
The current study suggests embedding of modelling in inquiry. Therefore, the purpose of this research was to empirically identify the effects of implementation of model-based inquiry on students' scientific process skills and conceptual knowledge. This study was framed theoretically by the Practice Framework which reflects model-based inquiry view of science. True-experimental design using quantitative research methods was carried out for the study. Participants of the research were pre-service physics teachers. Model-based inquiry was implemented in the experimental group while the control group worked in an inquiry-based environment. Therefore, guided inquiry was implemented in both groups but the control group did not build a model. The inquiry intervention lasted 10 weeks and was related to dynamics concepts. Data were collected by using the Integrated Process Skill Test and the Force Concept Inventory. The participants in both groups did not show any difference in their overall scores of scientific process skills and conceptual knowledge after the instruction However, when their scores of scientific process skills were compared in terms of the five dimensions in the test, it was found that while the control group increased their performances significantly in the dimensions of identifying variables and stating hypothesis, the experimental group improved their scores significantly in these two dimensions as well as in the dimensions of operational definitions and data and graph interpretations. This study adds to the limited research in the area of model-based inquiry by examining its effectiveness when used in a science classroom. (C) 2014 Published by Elsevier Ltd.
Keywords: Model-based inquiry; physics; science process skills; conceptual knowledge